ENTREPRENEURSHIP MOTIVATION BEHIND ENTREPRENEURSHIP INTENTION WITH A FAMILY BUSINESS BACKGROUND - Thusy Tiara Saraswati; Sudarmiatin; Agus Hermawan (Badan Penerbit STIEPARI Press, 2022)
A person's entrepreneurial intention is influenced by several factors which can be seen in an integral framework involving various internal factors, external factors, and contextual factors. Creating a job field requires a high and strong intention and motivation so that it can be realized. Apart from high intentions and motivation, it should also be accompanied by background. The purpose of this study is to determine the effect of the family business on entrepreneurial intention through entrepreneurial motivation. This research is a quantitative type with an explanatory descriptive. The research population was all Marble Craftsmen in Tulungagung of 267 Marble Craftsmen and obtained a sample of 157 respondents. The questionnaire used in this study is closed. The research scale used is the Likert Scale. Instrument trials use validity and reliability tests. Data analysis techniques using descriptive statistical analysis, path analysis, and hypothesis testing. The research results show that there is an influence of family business on entrepreneurial motivation. There is an influence of family business on entrepreneurial intention. There is an influence of entrepreneurial motivation on entrepreneurial intention. There is the influence of family business on entrepreneurial intention through entrepreneurial motivation